Velkommen til Merkolland – legitimeringsstrategier i den offentlige debat om eurokrisen - Just, Sine Nørholm (Politik, 2013)
The question of how to deal with the EU’s economic crisis is often reduced to two opposed positions: auster- ity measures vs. public investments, neatly represented by German Chancellor Angela Merkel and French President Francois Hollande, respectively. Merkel and Hollande also represent two di erent visions of EU- legitimacy in the broader sense: political integration vs. economic integration. at both the speci c and the general di erences between the two can be reconciled, is exempli ed by the European Council’s decisions to supplement the scal compact with a growth compact and to begin a process of political and economic reform. However, the proposed entwinement of political and economic legitimacy ignores the dimension of social legitimacy or solidarity among strangers, as Jürgen Habermas would put it. is paper explores how issues of identity and solidarity gure in the public debate about the Euro crisis. e main argument is that the politico-economic constitution of the EU as ‘Merkolland’ has, so far, rendered it a rather soulless place.